Exercício de experimentação comparada: um estudo sobre o imaginário social acerca dos processos de cura a partir do uso mágico-religioso das relíquias no contexto do Império Carolíngio e do Reino da França–Sécs. VIII e IX–X e XI Autor: Fabricio Nascimento de Moura - MOURA, Fabricio Nascimento de (2024)
The approach to the use of relics in healing rituals in the context of the Carolingian Empire and the Kingdom of France between the 8th and 11th centuries is part of the debate on the question of sanctity and religious and medical practices in medieval society. We question the meanings and symbolic value of these rites. To examine our corpus of documents, we used the methodology of content analysis. This study was also structured using the methodology of comparative experimentation proposed by Marcel Detienne, which establishes the possibility of building comparisons between societies that are distant in time and space. The comparative methodology, as well as the review of the theory on the relationship between Magic and Religion, allowed us to infer that the healing rites through the use of the relics of people who were considered saints in medieval society during the period mentioned above were magical-religious ceremonies whose intention was to overcome the stigma of the illness and reintegrate the person into the community.